Auxin inhibits chlorophyll accumulation through ARF7-IAA14-mediated repression of chlorophyll biosynthesis genes in Arabidopsis - Luo, Wei-Gui; Liang, Qi-Wen; Su, Yi; Huang, Chao; Mo, Bei-Xin; Yu, Yu; Xiao, Lang-Tao (Frontiers in Plant Science, 2023)
Auxin is a well-known important phytohormone in plant that plays vital roles in almost every development process throughout plant lifecycle. However, the effect of auxin on the metabolism of chlorophyll, one of the most important pigments involved in the photosynthesis, was intertwined and the underlying mechanism remained to be explored. Here, we found the auxin-defective yuc2 yuc6 double mutant displayed dark-green leaf color with higher chlorophyll content than wildtype, suggesting a negative regulatory role of auxin in chlorophyll biosynthesis. The chloroplast number and structure in mesophyll cells were altered and the photosynthetic efficiency was improved in yuc2 yuc6. In addition, the chlorophyll level was significantly improved during seedling de-etiolation in yuc2 yuc6 mutant, and decreased dramatically under IAA treatment, confirming the inhibitory role of auxin in chlorophyll biosynthesis. The analyses of gene expression in mature leaves and de-etiolation seedlings suggested that auxin suppressed the expression of many chlorophyll biosynthesis genes, especially PROTOCHLOROPHYLLIDE OXIDOREDUCTASE A (PORA) and GENOMES UNCOUPLED 5 (GUN5). Yeast-one-hybrid and luciferase assays demonstrated that the AUXIN RESPONSE FACTOR 2 (ARF2) and ARF7 bind to the promoter of PORA and GUN5 to suppress their expression with the help of INDOLE-3-ACETIC ACID14 (IAA14). Collectively, our research explicitly unraveled the direct inhibitory role of auxin in chlorophyll biosynthesis, and provided new insight into the interplay between auxin signaling and chlorophyll metabolism.